MAIN PROBLEMS AND PROSPECTS OF REPUBLIC OF BELARUS IN RESPECT OF ITS ENTRY TO INTERNATIONAL BOTTLED WATER MARKET - P. G. Nikitenko; G. T. Kulakov; Е. V. Skvortsova (Наука и техника)
The Republic of Belarus has significant reserves of ground fresh and mineral water. Consumption of bottled water in the world has a tendency of steady growth. In this regard, Belarus can increase production and sale of bottled water on the external  and domestic markets as well. The paper  describes main tendencies prevailing on the world market;  it contains an analysis of the normative and legal foundation on regulation of production and sale of bottled water in the Republic and abroad; the paper also estimates the possibilities to increase volume of export water.